Somatic chromosome number in nutmeg (Myristica fragans Boutt.) - KRISHNAMOORTHY, K P M DHAMAYANTHI, B (Journal of Spices and Aromatic Crops, 1999)
The somatic chromosome number in nutmeg (Myristica fragrans) was determined to be 38 in root tips, using squash technique.